Psychological well-being in patients undergoing stem cell transplantation - Berna Bayir; Rukuye Aylaz; Mehmet Ali Erkurt; Serap Bostanci (Acta Scientiarum. Health Sciences, 2022)
The aim of the study is to determine the psychological well-being of patients who underwent stem cell transplantation. This cross-sectional study was conducted with 100 patients. Data were collected face-to-face using an introductory information form and the Brief Symptom Inventory. When the results of the patients were examined, the interpersonal sensitivity of the sub-dimensions of the scale was found to be 5.0 ± 4.06, depression 7.60 ± 5.37, and anxiety disorder 7.90 ± 5.34. There was a significant difference between the diagnosis time of the patients and all sub-factors of the scale, except phobic anxiety. It was found that the psychological state of the patients was directly related to the time of first diagnosis. As a result, the importance of following the psychological process of the patients during the treatment process was revealed when planning nursing care.